PERANCANGAN TATA LETAK PADA GUDANG BAHAN PENGEMASAN DI PT PARAGON TECHNOLOGY AND INNOVATION - Arismunandar Suhartono, Kevin
PT Paragon Technology and Innovation (PTI) is a beauty and body care manufacturing company. Due to the increment of the number of products sold, PTI faces a new challenge in their packaging material warehouse. Currently, the warehouse consists of 2 main areas for two types of products, namely liquid, and decorative. Inaccuracies in determining the size of each area make some new This condition becomes 39.57% of the order delay causes. Therefore, PTI needs a new packaging material warehouse layout that will be able to minimize the picker order picking time with the current size warehouse limitation. The warehouse layout design process begins with determining the storage space requirements based on storage policies. The storage policies used in this research were existing storage policy, random storage policy, and class-based storage policy using FSN analysis (Devarajan & Jayamohan, 2016; Mitra, et al., 2015; Rosenwein, 1994) and cluster analysis (Nainggolan, et al, 2018). Based on the storage space requirement, warehouse layouts were designed according to their flow, which are U-flow (Cakmak, et al., 2012; Onut, et al., 2008) and flow-through (Cakmak, et al., 2012; Onut, et al., 2008). After that, the allocation of product classes in the warehouse with a class-based storage policy was determined (Muppani & Adil, 2008; Chan & Chan, 2011). The comparison between designs was based on the duration of the research, January 2020 to April 2021 (Muppani & Adil, 2008; Goetschalkx, 2012). The best alternative design is a U-flow warehouse with a class-based storage policy. This design has a capacity of 9664 pallets and the total expected travel time is 975.55 hours or 21.17% less than the current design. The total expected travel time of pickers is 516.08 hours or 26.49% less than the current design.